Religiously or Spiritually-Motivated Forgiveness and Subsequent Health and Well-Being among Young Adults: An Outcome-Wide Analysis - Chen, Ying (J Posit Psychol, 2018)
This study performs an outcome-wide analysis to prospectively examine the associations of forgiveness (including forgiveness of others, self-forgiveness and divine forgiveness) with a range of psychosocial, mental, behavioral and physical health outcomes. Data from the Nurses’ Health Study II and the Growing Up Today Study (Ns ranged from 5,246 to 6,994, depending on forgiveness type and outcome) with 3 or 6 years of follow-up were analyzed using generalized estimating equations. Bonferroni correction was used to correct for multiple testing. All models controlled for sociodemographic characteristics, prior religious service attendance, prior maternal attachment and prior values of the outcome variables. All forgiveness measures were positively associated with all psychosocial well-being outcomes, and inversely associated with depressive or anxiety symptoms. There was little association between forgiveness and behavioral or physical health outcomes. Forgiveness may be understood as a good itself, and may also lead to better subsequent mental health and psychosocial well-being.